Factors affecting the occurrence and abundance of the Natal Cascade frog Hadromophryne natalensis at Mariepskop South Africa - Ferguson, J. Willem H. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2016.